FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR MATEMATIKA SISWA UNTUK PENERAPAN BAHAN AJAR KONTEKSTUAL MENGINTEGRASIKAN PENGETAHUAN TERKAIT DAN REALISTIK - Helma, Helma; Edizon, Edizon (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Mathematics learning on high school should be associated with other sciences and everyday life. In this way, the mathematics learning is more realistic, interesting and meaningful. However, re-ality shows that mathematics learning materials has not been associated with other sciences and eve-ryday life. Initial research find that needs to be develop contextual mathematics material. Before the learning materials are prepared, it is important to know the characteristics of learners in following the learning of mathematics that affect the learning outcomes. There are five factors that influence the learning outcomes, namely background, interest, attitude, motivation and learning styles The purpose of research is to determine the factors that influence learning outcomes. Type of this research is de-scriptive research. The instruments are assessment sheets for learners characteristics and test. The results is factors that influence the learning outcomes of learners directly for the development needs of contextual mathematics teaching materials to integrate related knowledge and realistic approach is the learning style.